2009
DOI: 10.1016/j.bbrc.2008.11.103
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of cholesterol 24-hydroxylase by histone deacetylase inhibitors

Abstract: Keywords:24S-hydroxycholesterol CYP46A1 CYP39A1 Epigentics Histone deacetylase inhibitor Oxysterol Brain cholesterol a b s t r a c tThe mechanistic basis for the tissue specific expression of cholesterol elimination pathways is poorly understood. To gain additional insight into this phenomenon we considered it of interest to investigate if epigenetic mechanisms are involved in the regulation of the brain-specific enzyme cholesterol 24-hydroxylase (CYP46A1), a key regulator of brain cholesterol elimination. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
4
26
0
Order By: Relevance
“…The 0.12pGL2 promoter reporter construct was transfected in SH-SY5Y cells and 24 h after cells were arising from overexpressing this enzyme in a mouse model of AD ( 9 ). We and others have shown that HDACi are one of the few classes of compounds known to induce CYP46A1 expression ( 10,11 ). In our previous study, we showed that the histone deacetylase inhibitor TSA induced a transient histone hyperacetylation of CYP46A1 promoter, which signifi cantly increased CYP46A1 transcription in SH-SY5Y neuroblastoma cells ( 11 ).…”
Section: Okadaic Acid Inhibits Cyp46a1 Basal Expression In Nt2 Human mentioning
confidence: 99%
“…The 0.12pGL2 promoter reporter construct was transfected in SH-SY5Y cells and 24 h after cells were arising from overexpressing this enzyme in a mouse model of AD ( 9 ). We and others have shown that HDACi are one of the few classes of compounds known to induce CYP46A1 expression ( 10,11 ). In our previous study, we showed that the histone deacetylase inhibitor TSA induced a transient histone hyperacetylation of CYP46A1 promoter, which signifi cantly increased CYP46A1 transcription in SH-SY5Y neuroblastoma cells ( 11 ).…”
Section: Okadaic Acid Inhibits Cyp46a1 Basal Expression In Nt2 Human mentioning
confidence: 99%
“…This effect was time dependentmRNA levels were reduced during the first 24 hours of treatment but the suppression was lost by 48 hours. In contrast, Shafaati et al reported that in SH-SY5Y neuroblastoma cells, the levels of CYP27A1 mRNA increase by a factor of five following treatment with the same HDAC inhibitor [30]. A possible reason for this discrepancy is that HepG2 cells are known to express a relatively large amount of CYP27A1 mRNA in comparison to SH-SY5Y cells and the basal chromatin architecture may and accessory proteins, including HDACs, are likely to be different and respond differently to the broad acting HDAC inhibitor used in these studies.…”
Section: Cyp27a1mentioning
confidence: 89%
“…In this study they reported that HDAC inhibitor treatment led to an increase in the expression of Cyp46a1 mRNA by approximately ten-fold in primary cultures of mouse cortical neurons. Later contemporaneous studies by Shafaati et al and Nunes et al reported that HDAC inhibition led to a profound upregulation of the mRNA expression of CYP46A1 (over 50-fold) in several different cell systems [30,33]. In addition Shafaati et al also reported that treatment of mice with HDAC inhibitors modestly increased the expression of Cyp46a1 in murine liver [30].…”
Section: Cyp46a1mentioning
confidence: 97%
See 2 more Smart Citations